Political Engagement among Undergraduate Women of Color. Issue 5 (20th October 2019) - Ro, Hyun Kyoung; Kim, Sanga; Bergom, Inger
Abstract : Drawing from an intersectionality framework, we studied political engagement among undergraduate women of Color. Using multi-institutional data, we examined how women students' race/ethnicity and community service and service learning experiences related to involvement in political campaigns, political efficacy, and voting in the 2016 presidential election. We found that women of Color were less engaged politically along these measures, compared to White women. We offer implications for student affairs practitioners.